2004
DOI: 10.1007/s00431-004-1492-z
|View full text |Cite
|
Sign up to set email alerts
|

Congenital analbuminaemia: biochemical and clinical implications. A case report and literature review

Abstract: Congenital analbuminaemia is a rare disorder with remarkably mild signs and symptoms at all ages. Although often thought to be innocent, this disorder may have important clinical complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
98
1
14

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(117 citation statements)
references
References 23 publications
4
98
1
14
Order By: Relevance
“…Individuals with CAA undergo a series of compensatory mechanisms including an increase in alternative proteins, an increase in protein half-life and adjustments to the osmotic and hydrostatic pressure gradients (1). In the absence of serum albumin, hepatic cells compensate by increasing the biosynthesis of other plasma proteins, including α, β and γ proteins (5).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Individuals with CAA undergo a series of compensatory mechanisms including an increase in alternative proteins, an increase in protein half-life and adjustments to the osmotic and hydrostatic pressure gradients (1). In the absence of serum albumin, hepatic cells compensate by increasing the biosynthesis of other plasma proteins, including α, β and γ proteins (5).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that the half-life of infused albumin in individuals with CAA is prolonged by up to four-times, with the rate of degradation slowing as serum albumin levels decrease (2,12,13). The osmotic pressure gradient is maintained by the compensatory increase in plasma proteins, as well as by increased transcapillary fluid filtration and lymph drainage, and the reduced hydrostatic pressure gradient is achieved by lowered capillary blood pressure and increased interstitial hydrostatic pressures (1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations